Analysis of Solar Panel Energy Consumption on Tourist Boats in Labuan Bajo - Putra Pratama; Mohammad Danil Arifin (International Journal of Marine Engineering Innovation and Research, 2023)
Renewable energy is alternative energy that is currently being developed. In the current development of transportation, renewable energy is something that must be utilized properly in creating environmentally friendly modes of transportation. The use of renewable energy in the shipping industry plays a very important role in the era of the fossil fuel crisis. Research on this ship uses solar panels to convert solar energy into electrical energy, this energy can be used for ship navigation purposes. The ship's propulsion system uses an electric engine. The electric engine uses a battery that can be recharged when the ship is docked at the port. The solar panels used by Thin Film Solar Cells are lighter and have a high efficiency value. Total energy use for navigation is 799.6 kW. This ship uses 182 Thin Film Solar Cells with a capacity of 100 WP. This ship uses 4 batteries, where 1 main battery is used to drive the electric motor. Meanwhile, for backup energy storage, navigation uses 3 batteries.